Gender and Transformations: Female Activism in Tanure Ojaide’s The Activist - Ohagwam, Uchenna; Ogbuagu, Ndubuisi (Journal of Gender and Power, 2024)
There are some gender expectations and roles that are traditionally assigned to the woman which are both psychologically excruciating and potentially limiting. Many times, gender issues centre around male and female experiences; and the rationale behind feminist writings is to correct negative conceptions raised by male writers about women, and how women can recreate their world and rightly manage their social space. Over time in history, women have maintained that the decisions which men make, often have far-reaching consequences on them; to this end, they have chosen to get involved, questioning their roles, negotiating more roles, taking on greater responsibilities and are exploring newer approaches to addressing social problems. The study seeks to unravel some transformational endeavours of women in Tanure Ojaide’s The Activist. Through an analysis of samples of related reviews on gender writings, the paper explores practical strategies of women to seek redress and as such transition from the precarious margin of social experience to the centre. Drawing from nego-feminism theoretical framework, an African feminism strand developed by Obioma Nnaemeka, which consist chiefly in negotiation, balance, compromise, and complementarity; the analysis examines how women have negotiated their roles in their bid to make significant social changes and transformations.The article finds out that gender politics is graphically etched and dramatised in many African literary texts, but the form portrayed in Ojaide’s The Activist, is therapeutic, palliative and nurturing. It concludes by identifying gender stereotyping as a key impediment to gender and transformations.